Combination of Irreversible Electroporation and STING Agonist for Effective Cancer Immunotherapy - Go, Eun-Jin (Cancers (Basel), 2020)
SIMPLE SUMMARY: This study deals with a new strategy for effective cancer immunotherapy using a combination of electrical ablation and immune adjuvant, a stimulator of interferon genes (STING) agonist. The combination treatment significantly improved the cancer treatment effect by converting the immunosuppressive tumor microenvironment (TME) to an immunogenic TME. The combination of interventional oncology and immuno-oncology is expected to contribute to the treatment of various difficult-to-treat tumors. ABSTRACT: Recently, cancer immunotherapy has received attention as a viable solution for the treatment of refractory tumors. However, it still has clinical limitations in its treatment efficacy due to inter-patient tumor heterogeneity and immunosuppressive tumor microenvironment (TME). In this study, we demonstrated the triggering of anti-cancer immune responses by a combination of irreversible electroporation (IRE) and a stimulator of interferon genes (STING) agonist. Optimal electrical conditions inducing damage-associated molecular patterns (DAMPs) by immunogenic cell death (ICD) were determined through in vitro 2D and 3D cell experiments. In the in vivo syngeneic lung cancer model, the combination of IRE and STING agonists demonstrated significant tumor growth inhibition. We believe that the combination strategy of IRE and STING agonists has potential for effective cancer immunotherapy.